Characterising mobile phone calls while driving on limited-access roads based on SHRP 2 naturalistic driving data. (April 2020) - Kreusslein, Maria; Morgenstern, Tina; Petzoldt, Tibor; Keinath, Andreas; Krems, Josef F.
Highlights: Data from the SHRP 2 naturalistic driving study was used. Drivers spent 50% of the mobile phone handling time glancing off-road. Drivers compensated off-road glances to the detriments of on-road glances. Mean and maximum off-road-glances were below the 2 s critical threshold. Mobile phone storage location did not influence glance behaviour. Abstract: Research has found that mobile phone call engagement while driving negatively affects driving performance. However, no studies exist characterising hand-held mobile phone calls while driving under naturalistic conditions that include aspects such as the duration of mobile phone subtasks and glance behaviour. Identifying the particularly distracting phases of hand-held telephoning and the nature of influencing factors are the basis for developing design recommendations (e.g. for an in-vehicle information system). Potential influencing factors on driving performance such as call type, mobile phone storage location, or any self-regulatory behaviour need to be taken into account. The present study aimed to draw a comprehensive picture of making hand-held mobile phone calls while driving on limited-access roads using SHRP 2 naturalistic driving data. Mobile phone phase duration, glance behaviour, call type, and mobile phone storage location were coded manually across 98 events. The results show that the handling phase of a mobile phone call (e.g. searching for contacts, dialling) was the most dangerous due to longer mean off- than on-road glances. Outgoing calls caused longer mean off-road glances than incoming; nevertheless, the 2 s critical threshold was not exceeded. A significant influence of mobile phone storage location on glance behaviour did not exist. Moreover, at least in free-flow driving conditions, drivers had enough spare capacity to conduct a mobile phone call without reducing vehicle speed. The results suggest that in low complexity traffic situations drivers can compensate for the increased driving task demand due to telephoning by making minor changes in glance behaviour.